Wisata Halal di Gili Trawangan Lombok Utara - Muh Baihaqi (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2019)
This study aims to determine the implementation of halal tourism on Gili Trawangan and to determine the response of tourism actors to the implementation of Perda No. 2 of 2016 concerning Halal Tourism in the Gili Trawangan Region. This type of research is descriptive qualitative which takes data through observation, interviews and documentation. The concept of halal tourism on Gili Trawangan cannot be fully implemented in a short time, but it takes a long time because it is feared that it will have an impact on the number of foreign tourists visiting, especially those from Europe. The tourism actors respond to the application of halal tourism on Gili Trawangan with a diﬀ erent response. Some tourism operators accept the concept of halal tourism applied in Gili Trawangan, some disagree with oﬀ ering an alternative to the regulation being implemented in Gili Air or Gili Meno with the concept of shari'ah beach tourism. Some stated that the Halal Tourism Law is not suitable at all applied in coastal areas and only suitable for urban tourism.